The list of Adrian Messenger [videorecording (DVD)] - Scott, George C., 1927-1999; Douglas, Kirk, 1916-2020-; Curtis, Tony, 1925-2010; Lancaster, Burt, 1913-1994; Mitchum, Robert; Sinatra, Frank, 1915-1998; MacDonald, Philip (Universal Studios ; Universal Pictures Home Entertainment, 2017)
A retired officer must uncover the identity of a mass murderer who is killing off the potential heirs to a family fortune. The only clues are the names on the list of murdered heir Adrian Messenger. The tension builds as the final evil unfolds.